ENHANCING ACCOUNTING RESEARCH: HOW ARTIFICIAL INTELLIGENCE CHANGES THE GAME? - Hamzah N. Al-Jumaili (ZILLZELL MEDIA PRIMA, 2025)
This study explores artificial intelligence technology in the scientific research environment, as the researcher seeks to demonstrate the impact of artificial intelligence technology on the quality of scientific research within the framework of accounting sciences in the context of multiple countries represented by (Iraq, Egypt, Saudi Arabia, Jordan, Spain, Australia, Malaysia). The questionnaire tool was used to obtain an answer to a set of paragraphs related to the research variables represented by the dimensions of artificial intelligence and the quality of scientific research. 863 answers were obtained from the countries under study, and these data were subjected to statistical analysis using the SPSS-25 program. The conclusion was reached that artificial intelligence negatively affects the quality of scientific research within the framework of accounting sciences. The partial effects between the research variables and factors can be viewed in the results that were explored in the study. A set of detailed results related to the practices of using artificial intelligence in countries were reached, as we concluded that researchers tend to use artificial intelligence at a low level and may reach a moderate level, which gives an impression about the trend of current practices towards introducing innovative technologies in preparing scientific research in the field of accounting, as technology is used to enhance efficiency and improve results without full reliance on it. However, there is still a general reluctance to fully rely on artificial intelligence in the field of accounting sciences. Despite the potential benefits of the technology, such as increased efficiency and big data analysis, concerns about accuracy, deep understanding, and ethics hinder the general acceptance of full adoption; our study found that Saudi Arabia and Australia have a high level of practices of using artificial intelligence in a large part of the research preparation process. While in countries such as Iraq and Egypt, our results recorded the lowest use of this technology in the field of scientific research in accounting sciences.